Chosen aspects of quality of life in patients with venous leg ulcers - Michaela Miertová; Klaudia Dlugošová; Anna Ovšonková; Juraj Čáp (University of Ostrava, 2016)
Aim: The aim of the paper was to describe chosen aspects of quality of life in patients with venous leg ulcers treated at home in the Turiec region, and to find differences in assessing quality of life in relation to degree of adherence to external compression therapy. Design: A quantitative cross-sectional study. Methods: There were 61 patients with venous leg ulcers at 68.59 ± 9.49 years of age, with an average length of wound treatment of 6.34 ± 5.51 years. The adapted self-assessment questionnaire, the Freiburg Life Quality Assessment wound module (FLQA-w), was used to gain empirical data. Results: The findings revealed that the worst score was achieved in the category of everyday life (3.61 ± 0.93). Statistically significant differences were found between the group of respondents who apply bandages on a daily basis and those who did not use them at all. Regular bandage application is closely connected with positive assessment of wound therapy (p = 0.043), psychosocial life (p = 0.023), verbalisation of well-being in various categories (p = 0.001), assessment of state of the wound (p = 0.032), assessment of health condition (p = 0.019), and overall quality of life (p = 0.014). Length of wound treatment is related to assessments of quality of life. Conclusion: Non-healing wounds, the associated therapy and financial means required to treat them, and the pain resulting from them, are connected with physical difficulty, experience of negative emotions, and, thus, the worsening of patientsʼ quality of life. The results of the study could form the basis for further studies on similar issues.